Українська освітня студентська міграція в контексті глобалізаційних викликів - Ємельянова, Юлія; Yemelianova, Yuliia; Терещенко, Анастасія; Tereshchenko, Anastasya (Волинський національний університет імені Лесі Українки, 2020)
Глобалізація створила умови для вільного переміщення багатьох людей між країнами та континентами з метою працевлаштування, і це явище має стійкий характер: закриті сьогодні з приводу пандемії «Ковід-19» кордони завтра неминуче відкриються. Цьому сприяє головний економічний ефект глобалізації, який забезпечує більш розвинені держави дешевою робочою силою, а менш розвинуті долучає до сучасних технологій. Мільйони людей, у тому числі й молодь України, уже звикли до такого способу життя, який передбачає міграційні поїздки, іноді – довготривалі. Останніми роками стає помітною серед українських трудових мігрантів нова група – студентська молодь. У статті розглянуто цей соціальний факт із різних боків, проаналізовано його значення для сучасного українського суспільства, дано оцінку з позиції перспектив функціонування українського суспільства. Головним висновком є вказівка на майбутній системний структурний дисбаланс, що загрожує безпеці країни в цілому.
Ukrainian Educational Student Migration in the Context of Globalization Challenges
Globalization has led to the free movement of many people between countries and continents in order to find employment. This phenomenon is becoming permanent: the borders that are today closed due to the Covid-19 pandemic will inevitably open tomorrow. Opening of borders will facilitate the main economic «mechanism» of globalization, which brings cheap labour to more developed countries and introduces poor countries to modern technologies. Millions of people on the planet are already accustomed to this way of life, which involves migratory trips, often long-term. In the era of the current wave of globalization, the phenomenon of Ukrainian labour migration, whose history began at the end of the 19th century, receives a new dimension. Labour migrants from Ukraine are one of the largest groups of migrants in Europe. According to various estimates, their number has reached several million, and this is typical for developing countries, to which Ukraine can be attributed. Researchers note that the average age of Ukrainian migrants has dropped significantly in recent years. Most of them (over 40 %) are men aged 30–44. It is also important that more than a third of migrants have a higher education, but are often forced to agree to low qualifications jobs thereby lowering their social status. Young citizens of Ukraine are also getting used to migratory trips. After Ukraine has received a visa-free regime, they willingly use the freedom of movement to test the advantages and disadvantages of living abroad. Education in Europe has become popular; more and more often Ukrainian citizens with foreign diplomas enter the labour market. The authors analyze student educational migration and argue that in modern Ukraine this process should be subject to the control of both the authorities and public organizations. The authors argue that uncontrolled educational migration is becoming the first stage of labour migration that today is already leading to imbalances in the functioning of Ukrainian society.
Keywords: трудова міграція; студентська освітня міграція; глобалізація; інтелектуалізація праці; людський капітал; labour migration; student educational migration; globalization; intellectualization of labour; human capital; 316